The regeneration of palmiet (prionium serratum) following hydrogeomorphic disturbance: a case study of the Kromme River wetland - Van Eck, Caydon Daniël (Rhodes University, Faculty of Science, Department of Geography)
The Kromme River wetland in the Eastern Cape of South Africa occupies a broad valley (up to 350 m wide) with a gentle longitudinal slope of less than 2 % that has been formed by cut-and-fill cycles that are initiated by trunk-tributary interactions. These hydrogeomorphic disturbance events trigger gully erosion and generate sediments, the coarse fraction of which is deposited less than 2 km downstream, leading to depositional floodout features that fill gullies headwards. This process has been occurring at intervals for at least 10 000 years, and as such pre-dates the introduction of European farming practices in the area. Plants that regenerate by colonising these features are thought to have evolved adaptions necessary to colonise intermittently produced bare sandy sediments. This study aimed to examine the regeneration ecology of palmiet (Prionium serratum), the dominant vegetation community within these cut-and-fill wetlands, by relating its regeneration characteristics to environmental factors in a reach of the Kromme River wetland that has experienced a recent hydrogeomorphic disturbance event (approximately 10 years before the commencement of this study). Palmiet was found to be regenerating on sedimentary deposits on beds of gullies and on depositional bars on the margins of gully beds. The large depositional floodout downstream of a large gully also favoured palmiet regeneration, where it was found to be regenerating along not only the active channel, but also along old abandoned flow paths and sometimes areas well elevated above the channel. The geomorphic features that favoured palmiet regeneration were characterised by coarse-grained sediments (mean particle size approximately 310 Î¼m) with low organic matter content (0.61 %), a low depth to the water table and low elevation above the thalweg (mean depth to water table is approximately 0.6 m), and a relatively close distance to the thalweg (< 10 m). This understanding of palmiet's regeneration characteristics was viewed in relation to existing literature on undisturbed palmiet wetland plant communities and its reported contribution to conditions that favour wetland formation through gully filling, which allowed for the creation of a conceptual model of palmiet regeneration, colonisation and long-term persistence. This model was based on the Fluvial Biogeomorphic Succession concept. It suggests that palmiet's interaction with the hydrogeomorphic environment throughout the different stages of its life cycle results in self-organising biogeomorphic landforms. Over hundreds of years, the reciprocal interactions between palmiet, sediments and water, fills gullies and restores valley bottoms, ultimately leading to the formation of a wetland landform. It is further proposed that through continued accretion, the geomorphic wetland landscape becomes more and more disconnected from the hydrogeomorphic dynamics of the fluvial system, such that the prevailing conditions begin to favour fynbos establishment, which may outcompete palmiet.
Keywords: Biogeomorphology -- South Africa Kromme Estuary (Eastern Cape); Wetland ecology; Prionium serratum Regeneration; Fluvial geomorphology; River channels